Synthesis and Characterization of NiFe2O4/ZnO core-shell Nanocomposites - Khac Huy, Dinh; Phuc Duong, Nguyen; Thanh Loan, To; Chung, Hoang Manh; Kim Thanh, Nguyen; Van Khai, Vu (VNU Journal of Science: Mathematics - Physics; Vol 34 No 4DO - 10.25073/2588-1124/vnumap.4297, 2018)
NiFe 2 O 4 /ZnO core-shell nanocomposites were prepared by two-step methodology. First, NiFe 2 O 4 nanoparticles as the cores were synthesized by using hydrothermal method, and then modified by sodium citrate. After that ZnO as the shell was coated on modified NiFe 2 O 4 nanoparticles by two different chemical methods including hydrothermal and co-precipitation. The formation, crystal structure, morphology and magnetic properties of the uncoated and coated samples were investigated by using X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy and vibrating sample magnetometer. It was shown that the core nanoparticles are single phase of NiFe 2 O 4 with cubic spinel structure. Sodium citrate was well bonded on the surface of the modified nanoparticles. Contributions of the phases in the coated samples as well as structural parameters were determined from XRD data on applying of Rietveld refinement analysis. Magnetization of the core can be improved by adjusting the modification steps. XRD analysis result and SEM images revealed the formation of core/shell structure in the sample coated by using co-precipitation method.